Transparency and Language Contact: the Case of Haitian Creole, French and Fongbe (Linguistics in Amsterdam, 2018)
When communicating, speakers map meaning onto form. It would thus seem obvious for languages to show a one-to-one correspondence between meaning and form, but this is often not the case. This perfect mapping, i.e. transparency, is indeed continuously violated in natural languages, giving rise to zero-to-one, one-to-many and many-to-one opaque correspondences between meaning and form. However, transparency is a mutating feature, which can be influenced by language contact. In this scenario languages tend to evolve and loose some of their opaque features, becoming more transparent. This study investigates transparency in a very specific contact situation, namely that of a creole, Haitian Creole, and its sub- and superstrate languages, Fongbe and French, within the Functional Discourse Grammar framework. We predict Haitian Creole to be more transparent than French and Fongbe and investigate twenty opacity features, divided into four categories, namely Redundancy (one-to-many), Fusion (many-to-one), Discontinuity (one meaning is split in two or more forms) and Form-based Form (forms with no semantic counterpart: zero-to-one). The results indeed prove our prediction to be borne out: Haitian Creole only presents four opacity features out of twenty, while French presents nineteen and Fongbe nine. Furthermore, the opacity features of Haitian Creole are also present in the other two languages.